Expression Profile of p53 and p21 in Large Bowel Mucosa as Biomarkers of Inflammatory-Related Carcinogenesis in Ulcerative Colitis. (7th August 2016) - Popp, Cristiana; Nichita, Luciana; Voiosu, Theodor; Bastian, Alexandra; Cioplea, Mirela; Micu, Gianina; Pop, Gabriel; Sticlaru, Liana; Bengus, Andreea; Voiosu, Andrei; Mateescu, Radu Bogdan
Abstract : Ulcerative colitis (UC) is a chronic, relapsing inflammatory bowel disease that slightly increases the risk of colorectal cancer in patients with long-standing extended disease. Overexpression of p53 and p21 in colonic epithelia is usually detected in UC patients when no dysplasia is histologically seen and it is used by pathologists as a discriminator between regenerative changes and intraepithelial neoplasia, as well as a tissue biomarker useful to predict the risk of evolution toward malignancy. We present a one-year prospective observational study including a cohort of 45 patients with UC; p53 and p21 were evaluated in epithelial cells. p53 was positive in 74 samples revealed in 5% to 90% of epithelial cells, while 63 biopsies had strong positivity for p21 in 5% to 50% of epithelial cells. Architectural distortion was significantly correlated with p53 overexpression in epithelial cells. Thus, we consider that architectural distortion is a good substitute for p53 and p21 expression. We recommend use of p53 as the most valuable tissue biomarker in surveillance of UC patients, identifying the patients with higher risk for dysplasia. Association of p21 is also recommended for a better quantification of risk and for diminishing the false-negative results.